2018
DOI: 10.1039/c7ra12042g
|View full text |Cite|
|
Sign up to set email alerts
|

Long non-coding RNA PVT1 facilitates cell proliferation by epigenetically regulating FOXF1 in breast cancer

Abstract: Plasmacytoma variant translocation 1 (PVT1) expression was elevated in breast cancer tissues and correlated to breast cancer progression and prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
(39 reference statements)
0
5
1
Order By: Relevance
“…PVT1 has been described in other types of cancer to act in the nucleus; thus, in ovarian cancer PVT1 represses miR-214 expression by recruiting EZH2 to its promoter [ 25 ], and in non-small cell lung cancer (NSCLC) PVT1 inhibits the expression of Large Tumor Suppressor Kinase 2 ( LATS2 ) by recruiting EZH2 to the LATS2 promoter [ 26 ]. In other tissues such as breast cancer [ 27 ], hepatocellular carcinoma [ 28 ], gastric cancer [ 29 ], and cholangiocarcinoma [ 30 ], PVT1 has been shown to interact with EZH2 and epigenetically inhibit the expression of some target genes. In fact, no description of PVT1 involvement with large-scale repression of gene expression has been published.…”
Section: Introductionmentioning
confidence: 99%
“…PVT1 has been described in other types of cancer to act in the nucleus; thus, in ovarian cancer PVT1 represses miR-214 expression by recruiting EZH2 to its promoter [ 25 ], and in non-small cell lung cancer (NSCLC) PVT1 inhibits the expression of Large Tumor Suppressor Kinase 2 ( LATS2 ) by recruiting EZH2 to the LATS2 promoter [ 26 ]. In other tissues such as breast cancer [ 27 ], hepatocellular carcinoma [ 28 ], gastric cancer [ 29 ], and cholangiocarcinoma [ 30 ], PVT1 has been shown to interact with EZH2 and epigenetically inhibit the expression of some target genes. In fact, no description of PVT1 involvement with large-scale repression of gene expression has been published.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, lncPVT1 is described as a chromatin modifier [71]. It has been demonstrated to bind the histone methyltransferase Enhancer of Zeste Homolog-2 (EZH2), a catalytic subunit of polycomb-repressive complex 2 (PRC2), leading to the direct histone methylation of several gene promoters, including the angiopoietin-like 4 (ANGPTL4) in cholangiocarcinoma [70] and trophoblast cells [72], the thyroidstimulating hormone receptor (TSHR) in thyroid carcinoma [73], the forkhead box f1 (FOXF1) in breast cancer [74], the large tumour suppressor kinase 2 (LATS2) in non-small-cell lung cancer (NSCLC) [49], the tumour suppressors p15 and p16 in GC [66], the miR-146a in prostate cancer [75], the miR-200c in melanoma [76], and the miR-200b in cervical cancer [77]. lncPVT1 could also recruit DNMT1 via EZH2 and promote DNA methylation of the miR-18b-5p promoter in gallbladder cancer (GBC) [68].…”
Section: Two Molecules Same Function?mentioning
confidence: 99%
“…Another example is PVT1, which acts as an oncogenic lncRNA in cancers, including BC. Guo et al showed that PVT1 inhibits the expression of the tumor suppressor gene FOXF1 by recruiting EZH2, a catalytic subunit of the PRC2 complex, consequently, increasing H3K27me3 levels in BC ( Guo et al, 2018 ). Last but not least, coming into interactions with chromatin-modifying enzymes not only serves scaffolding and recruitment functions but also may lead to degradation of the proteins and their complexes, as is the case in ANCR, which affects EZH2 stability and inhibits epithelial-mesenchymal transition (EMT), invasion, tumorigenesis and distant metastasis in BC ( Li Z. et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%